DAMPAK MEDIA SOSIAL TIKTOK TERHADAP KETERAMPILAN BERBAHASA SISWA KELAS V SD NEGERI 0607 PAGARAN BATU - Daulay, Irma Sari; Siregar, Lailan Aprina; Aminah Hasibuan (Yayasan Perguruan Kampus, 2025)
Based on the results of the study, it can be concluded that: (1) The language skills of grade V students of SD Negeri 0607 Pagaran Batu are good. Although there are still some students who are lacking in several indicators, for example, the intonation of the voice is still lacking, the correct pronunciation of vowels, and the lack of fluency in speaking. However, students' language skills changed after watching the TikTok video. The changes that occur are related to the language students use in everyday life. The existence of the TikTok application can change student behavior, especially in the style of speech that students see on TikTok and students imitate it. (2) The Impact of TikTok Social Media on the Language Skills of Grade V Students of SD Negeri 0607 Pagaran Batu includes: enriching students' vocabulary and can be used as a medium in learning foreign languages, for example English and Arabic. In addition, the use of TikTok can also increase creativity in the use of language and students' social interactions. TikTok encourages users to be creative with language, for example through poetry, songs, or comedy sketches, which can strengthen students' language and literacy skills. Then another positive impact is that it can be used in cultural learning. Videos on TikTok often reflect the culture of different countries, allowing students to learn about different cultural contexts and how language is used in those situations. The negative impacts of using TikTok on the language skills of grade V of SD Negeri 0607 Pagaran Batu include the use of non-standard language and grammatical errors. TikTok can improve students' language skills, but the language used is not grammatical, sounds rude and impolite. In addition, TikTok also has an impact on the lack of real social interaction. Excessive involvement with TikTok can reduce the time students spend interacting directly with friends, family, and teachers, which is important for the development of healthy language skills.